THE APPLICATION OF SIMPLE ADDITIVE WEIGHTING AND PROFILE MATCHING METHODS AS A SUPPORT FOR STUDENT ADMISSIONS AT SMK MUHAMMADIYAH TASIKMALAYA - Dani Rohpandi; Yuda Purnama Putra; Egi Badar Sambani (Journal of Multimedia Technology and Applied Software, 2024)
Most of the junior high school graduates want to continue their education to vocational schools, this can be evidenced by the large number of junior high school graduates who take the entrance exam to vocational schools. The unfortunate thing is that they are not mature in choosing a major. This kind of situation has an impact on the education costs that have already been incurred, both by the parents of the students and by the government that subsidizes the school to be useless because the student does not have adequate abilities for the major he has chosen, sometimes there are students who drop out. Based on the information obtained from the new student admission committee, the number of departments at SMK Muhammadiyah Tasikmalaya City consists of five majors, namely the department of light vehicle engineering, software engineering, network computer engineering, motorcycle engineering and marketing. The major is based on the student's choice when registering by listing their interests for major 1 and major 2. In addition, the major is determined by grades. The system to support the decision of admission and selection of majors with the Simple Additive Weighting (SAW) method and Profile Matching, is expected to help the admission committee of new students in determining majors for students. This decision support system is web-based so that it can be accessed anywhere by prospective students to register online, then the data will be processed to determine the right major for each student.